THE EFFECT OF PROFITABILITY, LEVERAGE, INSTITUTIONAL OWNERSHIP, MANAGERIAL OWNERSHIP, AND DIVIDEND POLICY ON FIRM VALUE - Wisnu Yuwono; Dita Aurelia (Journal of Global Business and Management Review, 2021)
This study aims to examine the effect of profitability, leverage, institutional ownership, managerial ownership, and dividend policy on firm value controlled by firm size. The sample of this study used 170 manufacturing companies listed on the Indonesian Stock Exchange from 2014 to 2018 which were selected using a purposive sampling method. The research method used was multiple linear regression analysis. The program used is the SPSS version 24 program. The results of the study indicate that profitability, institutional ownership, managerial ownership and dividend policy are significantly positive with firm value, leverage is negatively related to firm value. As a control variable, firm size has a significant positive effect on firm value.